2021
DOI: 10.1126/scitranslmed.abi7428
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal SARS-CoV-2 infection elicits sexually dimorphic placental immune responses

Abstract: Maternal SARS-CoV-2 infection drives sexually dimorphic placental immune responses and reduces SARS-CoV-2–specific antibody transfer to male fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 100 publications
(90 citation statements)
references
References 124 publications
6
71
3
Order By: Relevance
“…By quantifying anti-SARS-CoV-2 antibody titers and functions in the maternal and cord blood sera, the authors found that the mothers carrying male fetuses had lower maternal and cord blood titers than mothers carrying female pregnancies. Moreover, the transplacental transfer of IgG against other infectious agents, including influenza and pertussis, was not affected in male versus female pregnancies ( 95 ). No evidence of SARS-CoV-2-specific IgM in newborns was reported, supporting that vertical transmission of SARS-CoV-2 is uncommon ( 94 96 ).…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)...mentioning
confidence: 99%
“…By quantifying anti-SARS-CoV-2 antibody titers and functions in the maternal and cord blood sera, the authors found that the mothers carrying male fetuses had lower maternal and cord blood titers than mothers carrying female pregnancies. Moreover, the transplacental transfer of IgG against other infectious agents, including influenza and pertussis, was not affected in male versus female pregnancies ( 95 ). No evidence of SARS-CoV-2-specific IgM in newborns was reported, supporting that vertical transmission of SARS-CoV-2 is uncommon ( 94 96 ).…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)...mentioning
confidence: 99%
“…In translational work by Bordt et al, mothers carrying male fetuses had lower maternal IgG antibodies and transfer ratio following SARS-CoV-2 infection than pregnancies with female fetuses 18 . The possibility that fetal sex modifies maternal antibody response or placental transfer is intriguing.…”
Section: Discussionmentioning
confidence: 95%
“…CXCL10 (C-X-C motif chemokine ligand 10) is a pro-inflammatory chemokine secreted in response to interferon gamma (IFNγ) involved in the stimulation of monocytes, natural killer, and T-cells. Previous investigations have also reported CXCL10 gene expression upregulation in bronchoalveolar lavages [57], nasopharyngeal swabs [58] and male placentas exposed to maternal SARS-CoV-2 infection [43]. Importantly, CXCL10 may also be a key regulator of the “cytokine storm” in response to SARS-CoV-2 infection and circulating levels of CXCL10 are reported to be positively associated with disease severity [59-61].…”
Section: Discussionmentioning
confidence: 97%